PRISM protocol: a randomised phase II trial of nivolumab in combination with alternatively scheduled ipilimumab in first-line treatment of patients with advanced or metastatic renal cell carcinoma - Hannah L. Buckley; Fiona J. Collinson; Gemma Ainsworth; Heather Poad; Louise Flanagan; Eszter Katona; Helen C. Howard; Geraldine Murden; Rosamonde E. Banks; Joanne Brown; Galina Velikova; Tom Waddell; et al. (BMC Cancer, 2019)
Abstract Background The combination of nivolumab, a programmed death-1 (PD-1) targeted monoclonal antibody, with the cytotoxic T-lymphocyte antigen-4 (CTLA-4) targeted antibody, ipilimumab, represents a new standard of care in the first-line setting for patients with intermediate- and poor-risk metastatic renal cell carcinoma (mRCC) based on recent phase III data. Combining ipilimumab with nivolumab increases rates of grade 3 and 4 toxicity compared with nivolumab alone, and the optimal scheduling of these agents when used together remains unknown. The aim of the PRISM study is to assess whether less frequent dosing of ipilimumab (12-weekly versus 3-weekly), in combination with nivolumab, is associated with a favourable toxicity profile without adversely impacting efficacy. Methods The PRISM trial is a UK-based, open label, multi-centre, phase II, randomised controlled trial. The trial population consists of patients with untreated locally advanced or metastatic clear cell RCC, and aims to recruit 189 participants. Participants will be randomised on a 2:1 basis in favour of a modified schedule of 4 doses of 12-weekly ipilimumab versus a standard schedule of 4 doses of 3-weekly ipilimumab, both in combination with standard nivolumab. The proportion of participants experiencing a grade 3 or 4 adverse reaction within 12 months forms the primary endpoint of the study, but with 12-month progression free survival a key secondary endpoint. The incidence of all adverse events, discontinuation rates, overall response rate, duration of response, overall survival rates and health related quality of life will also be analysed as secondary endpoints. In addition, the potential of circulating and tissue-based biomarkers as predictors of therapy response will be explored. Discussion The combination of nivolumab with ipilimumab is active in patients with mRCC. Modifying the frequency of ipilimumab dosing may mitigate toxicity rates and positively impact quality of life without compromising efficacy, a hypothesis being explored in other tumour types such as non-small cell lung cancer. The best way to give this combination to patients with mRCC must be similarly established. Trial registration PRISM is registered with ISRCTN (reference ISRCTN95351638, 19/12/2017). Trial status At the time of submission, PRISM is open to recruitment and data collection is ongoing.